2013
DOI: 10.1016/j.sleep.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic correlations in 172 cases of rapid eye movement sleep behavior disorder with or without a coexisting neurologic disorder

Abstract: Objective To determine the pathologic substrates in patients with rapid eye movement (REM) sleep behavior disorder (RBD) with or without a coexisting neurologic disorder. Methods The clinical and neuropathologic findings were analyzed on all autopsied cases from one of the collaborating sites in North America and Europe, were evaluated from January 1990 to March 2012, and were diagnosed with polysomnogram (PSG)-proven or probable RBD with or without a coexisting neurologic disorder. The clinical and neuropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
230
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(244 citation statements)
references
References 112 publications
5
230
0
9
Order By: Relevance
“…Our results are consistent with previous studies that demonstrate increased prevalence of RSWA in patients taking antidepressants. 15,20,21 We also found that this increased risk is not due to age, gender, and type of SSRI/SNRI or presence of OSA. The most recent theories about REM sleep initiation advocate for a double switch model that may be triggered by neurons that are located in the brainstem.…”
Section: Discussionsupporting
confidence: 55%
“…Our results are consistent with previous studies that demonstrate increased prevalence of RSWA in patients taking antidepressants. 15,20,21 We also found that this increased risk is not due to age, gender, and type of SSRI/SNRI or presence of OSA. The most recent theories about REM sleep initiation advocate for a double switch model that may be triggered by neurons that are located in the brainstem.…”
Section: Discussionsupporting
confidence: 55%
“…Of the 21 with dementia, 18 had $1 cardinal parkinsonism manifestation (11 met full UK Brain Bank criteria for parkinsonism 23 ), and the remaining 3 had abnormal quantitative motor testing; therefore, most, if not all, had DLB. 11,16,24 Of 17 patients with PD, 8 had MCI at diagnosis. Therefore, we observed considerable overlap between parkinsonian and cognitive signs.…”
Section: Resultsmentioning
confidence: 99%
“…Two of these patients had postmortem studies and both had DLBD. Because idiopathic RBD can precede the onset of DLB by many years, 39 this raises the question of whether a history of probable RBD in the context of dementia should be diagnosed as DLB in the absence of other core features, even in the presence of memory impairment. With the current DLB criteria, patients with RBD and dementia may incorrectly be designated as clinically probable AD.…”
Section: 33mentioning
confidence: 99%